Selected complaint resolution bodies in Malaysia - Ali Mohamed, Ashgar Ali; Eishan Jan, Mohammad Naqib; Kamarudin, Abdul Rani; Ahmad, Muhamad Hassan (CLJ Publication, 2020)
After the establishment of the United Nations (UN), it adopted the Universal Declaration of Human Rights 1948 (UDHR) which was meticulously crafted by representatives from different legal and cultural backgrounds from all regions of the world. The UDHR sets out universally protected fundamental human right